Number of Compatible Pair of Actions For Finite Cyclic Groups of 3-Power Order - Shahoodh, Mohammed Khalid; Yuhani, Yusof; Sahimel Azwal, Sulaiman (United Kingdom Simulation Society, 2017)
Compatible actions are important in determining the non-abelian tensor product. Different compatible pair of actions gives a different tensor product even for the same group. The purpose of this paper is to determine the exact number of compatible pair of actions for the finite cyclic groups of 3-power order. By using some properties of number theory, the number of the compatible pair of actions for finite cyclic groups of 3-power order with a specific order of actions is determined and given as a main result in this paper.